Avaliação numérica não linear do efeito da modelagem da interface Concreto-PRFC em pilares curtos de concreto - Filgueira, Daniel Lucas (2018)
Several pathologies can occur in concrete structures, resulting from the natural aging of the material, the action of aggressive external agents or low quality control. One of the ways to reinforce the pillars is through carbon fiber jacketed. This technique has the advantages of easy handling and application, as well as low carbon specific fibers, high tensile strength, high modulus of elasticity and good resistance to chemical agents in general. In circular cross sections, the confinement pressure from the fiber is evenly distributed in the pillar, whereas in rectangular sections, there is concentration of stresses in the corners, requiring that they be rounded. As there is no official standardization in Brazil, many professionals do not use the technique due to lack of knowledge or insecurity. Generally, the reinforcement is scaled only through the professional's experience or use of manufacturers manuals. In this work, the behavior of carbon fiber reinforced concrete pillars (PRFC) is evaluated numerically, taking into account the contact interaction between the concrete and the PRFC layer. This contact is modeled in three different ways that are: perfect contact, cohesive surface and interface elements. In this work, concrete is represented by Concrete Damaged Plasticity (CDP), which is a model of physical nonlinearity, where a combination of the theory of plasticity and damage is represented, and the PRFC is represented by a linear isotropic behavior, validating this model through numerical and experimental examples in the literature. The models are validated through experimental tests found in the literature, obtaining a good agreement. Based on the analyzes performed, it was found that the jacket of short columns with PRFC is a good way to increase its compressive strength. In the study of the contact between the concrete and the PRFC, it was verified that the perfect contact and the cohesive surface are good types of contact elements, however, the interface elements did not present good results in the eccentric compression analyzes of prismatic pillars, therefore, the use of the cohesive surface is suggested if one intends to study the degradation of contact.